2010
DOI: 10.1158/1055-9965.epi-09-0581
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Error in Gas Chromatography-Mass Spectrometry–Based Quantification of Hydrolyzed Urinary Steroids

Abstract: Gas chromatography-mass spectrometry-based metabolite profiling can lead to an understanding of various disease mechanisms as well as to identifying new diagnostic biomarkers by comparing the metabolites related in quantification. However, the unexpected transformation of urinary steroids during enzymatic hydrolysis with Helix pomatia could result in an underestimation or overestimation of their concentrations. A comparison of β-glucurondase extracted from Escherichia coli revealed 18 conversions of 84 steroid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Indeed, previous studies demonstrated that the use of Helix pomatia juice can produce misleading results due to the presence of other enzymes that are responsible for steroids conversion [48, 49] that could affect the correct determination of 17 α -T, AED, DHEA, DHT, and ETIO. This different approach was used for the secondary goal of performing multivariate analyses based on the urinary profile of endogenous steroids to develop a probabilistic model able to discriminate treated animals from nontreated ones.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous studies demonstrated that the use of Helix pomatia juice can produce misleading results due to the presence of other enzymes that are responsible for steroids conversion [48, 49] that could affect the correct determination of 17 α -T, AED, DHEA, DHT, and ETIO. This different approach was used for the secondary goal of performing multivariate analyses based on the urinary profile of endogenous steroids to develop a probabilistic model able to discriminate treated animals from nontreated ones.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a b-glucuronidase solution for enzymatic hydrolysis was used to prevent the systematic error that can arise from the unexpected transformation of 3b-hydroxysteroids to 3-oxo-steroids with b-glucuronidase/arylsulfatase extracted from Helix pomatia, thus leading to a misinterpretation of clinical implications. 32 Because of its very polar structure, the recovery of 6b-OH-F with MTBE extraction was relatively low compared with that of other hydroxysteroids, but its urinary concentration remained quantifiable.…”
Section: Discussionmentioning
confidence: 99%
“…18,32 Briefly, the urine samples (2 mL) were spiked with 20 mL of the 6 IS mixtures (d 4 -androsterone, 40 mg/mL; d 3 -testosterone, 4 mg/mL; d 4 -17b-estradiol, 2 mg/mL; d 8 -17a-hydroxyprogesterone, 5 mg/mL; and d 9 -progesterone and d 4 -cortisol, 10 mg/mL), and they were then extracted with Oasis HLB SPE cartridges at a low flow rate (,1 mL/min). After each sample was loaded onto the cartridge, it was washed with 2 mL of water and eluted twice with 2 mL of methanol.…”
Section: Sample Preparationmentioning
confidence: 99%
“…One of the most reported derivatization techniques in steroid profiling is the application of a mixture of MSTFA/ammonium iodide (NH 4 I)/dithioerythritol (DTE) in a ratio of 500:4:2 (v/w/w) ( Moon et al . 2009 , 2010 , Jung et al . 2011 , Son et al .…”
Section: Analytical Techniques For Sex Steroid Metabolomementioning
confidence: 99%